"Goodbye … Through a Glass Door": Emotional Experiences of Working in COVID-19 Acute Care Hospital Environments. Issue 1 (March 2021) - Lapum, Jennifer; Nguyen, Megan; Fredericks, Suzanne; Lai, Sannie; McShane, Julie
Background: The severity of the COVID-19 health crisis has placed acute care nurses in dire work environments in which they have had to deal with uncertainty, loss, and death on a constant basis. It is necessary to gain a better understanding of nurses' experiences to develop interventions supportive of their emotional well-being. Purpose: The purpose of this study is to explore how nurses are emotionally affected working in COVID-19 acute care hospital environments. The research question is: What is the emotional experience of nurses working in COVID-19 acute care hospital environments? Methods: We employed a narrative methodology that focused on participants' stories. Twenty registered nurses, who worked in six hospitals in the Greater Toronto Area in Canada, participated in interviews. A narrative analysis was conducted with a focus on content and form of stories. Results: We identified three themes about working in COVID-19 acute care hospital environments: the emotional experience, the agency of emotions, and how emotions shape nursing and practice. Conclusion: In moving forth with pandemic preparations, healthcare leaders and governments need to make sure that a nurse's sacrifice is not all-encompassing. Supporting nurses' emotional well-being and resilience is necessary to counterbalance the loss and trauma nurses go through.